Utopia and Anthropocene: Capitalism and Societal Intersections in Margaret Atwood’s MaddAddam Trilogy (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
Margaret Atwood’s trilogy — Oryx and Crake (2003), The Year of the Flood (2009), and MaddAddam (2013) — depicts a dystopian landscape in which technological manipulation and the unchecked expansion of capitalism converge within a weakened state increasingly governed by powerful corporations. This dystopian scenario, often understood as the aftermath of failed utopian aspirations, foregrounds social inequality, environmental devastation, resource scarcity, and systemic violence as consequences of a neoliberal turn. At the same time, the proliferation of technological innovations fosters a transhumanist ideal of human enhancement, estranging bodies from their organic foundations. The aim of this article is to examine how human activity, as a (de)structuring force of social and ethical environments, has shaped the Anthropocene, ultimately presenting nonhuman bodies as a potential locus of hope for reimagining society. Keywords:Dystopia; Utopia; Anthropocene; Capitalism; Society.